Design of Monitoring System Step Walking With MPU6050 Sensor Based Android - Diah Ayu Fitriani; Wahyu Andhyka; Diah Risqiwati (Universitas Muhammadiyah Sidoarjo, 2017)
Walking is said to increase endurance, burn calories and improve cardiovascular health. To monitor the steps when walking, we need a tool that is a gyroscope sensor MPU6050. Making this tool uses a gyroscope sensor for monitoring footsteps because Gyroscope is used to measure or determine the orientation of an object based on the provisions of angular momentum. This tool has been tested by foot with a number of different steps. The device test carried out by one person testers.Data obtained from these tests resulting from the detection lower limit value and upper limit value of X axis angle data is used in data processing is the value of the X-axis is converted into a sine wave form chart. To detect footsteps, each wave has the upper value limit is 20o and the bottom value is -20o. Once the step is detected, these measures will be multiplied by the width of the foot when walking, then obtained distance